EVALUATION OF ACCOUNTING INFORMATION SYSTEMS IN SUPPORTING INTERNAL CONTROL (Proceeding of SINERGY, 2026)
Accounting Information System (AIS) is a system designed to collect, record, process, and present financial information that management needs to make decisions. It also serves as a tool for internal control within an organization. Internal control helps ensure that the organization's goals are met, especially in terms of reliable financial reports, protection of assets, and compliance with policies and regulations. A well-implemented Accounting Information System is expected to strengthen internal control and reduce the risk of errors or fraud in the accounting process.This study aims to assess the application of the Accounting Information System in supporting internal control within an organization and to identify the challenges faced during its implementation. The research method used is descriptive qualitative, which seeks to systematically and thoroughly describe the actual situation of the Accounting Information System's application and its role in internal control. Data collection was carried out through direct observation of accounting processes, semi-structured interviews with individuals involved in managing the Accounting Information System and internal control, as well as a document study of existing procedures and policies.This study aims to assess the application of the Accounting Information System in supporting internal control within an organization and to identify the challenges faced during its implementation. The research method used is descriptive qualitative, which seeks to systematically and thoroughly describe the actual situation of the Accounting Information System's application and its role in internal control. Data collection was carried out through direct observation of accounting processes, semi-structured interviews with individuals involved in managing the Accounting Information System and internal control, as well as a document study of existing procedures and policies.Accounting Information Systems (AIS) are important for giving accurate, useful, and up-to-date financial information that helps a company's internal control work well. Strong internal control is needed to make sure financial reports are trustworthy, protect the company's resources, and follow all relevant rules and guidelines. This study looks at how Accounting Information Systems are being used to support internal control in an organization. The research uses a qualitative descriptive approach, gathering data through observation, interviews, and reviewing documents. The findings show that the Accounting Information System has helped make internal control more effective, especially in areas like separating responsibilities, approving transactions, and keeping accurate records. But there are still some issues, like not enough skilled people and not fully using available technology. So, the company should work on improving the skills of its staff and keep developing the system so that internal control can be even better.